Science as a rational doxa. J. Życiński’s understanding of science and philosophy of science – beyond internalism and externalism - Liana, Zbigniew (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
Philosophical interests of Joseph Życiński (1948-2011) in the domain of the philosophy of science were focused on the debate concerning the nature of science and philosophy of science that followed the Einstein-Planck revolution in science. The unexpected discovery of the philosophical, extra-scientific presuppositions in science, as well as of the extra-rational factors determining the way these presuppositions are accepted in science were to be explained within the meta-scientific framework. It is the aim of this paper to present ˙ Życiński’s diagnosis of this post-revolutionary situation in the philosophy of science as well as his critique of the metascientific answers to this challenge. The reasons will be given why all those answers are put under two dichotomous rubrics of internalism and externalism. It will be also explained how Życiński intends to supersede this false in his opinion opposition with a new concept of the doxatic rationality. However, the details of the metascientific proposal of Życiński will be given only in the subsequent paper. In order to perform the aim of the paper the metatheoretic tools set out by Popper (1979) will be used.
Keywords: rationalism; skepticism; internalism; externalism; metascience; scientific revolution; metascientific revolution; philosophy of science